Spin-dependent electron reflection at W(110). (29th December 2020) - Angrick, C; Braun, J; Ebert, H; Donath, M
Abstract: Spin-dependent reflection of low-energy electrons at the W(110) surface caused by spin–orbit interaction was studied experimentally and theoretically. Comprehensive information for a wide range of electron incidence angles and energies was collected via maps for the reflectivity, the spin-dependent reflection asymmetry, and the figure of merit of the spin separation. The experimental results are compared with calculations of the scattering process using a realistic surface potential barrier. The results are discussed in view of possible applications of W(110) as a scattering target in spin-polarization detectors. Possible working points for use in single- as well as multi-channel spin-polarization-detection devices are identified and discussed.